The Effect of Entrepreneurial Skills and Business Mentoring on Startup Growth and Success in West Java - Sulandjari, Kuswarini (The Es Economics and Entrepreneurship, 2023)
This study investigates the dynamic interplay between entrepreneurial skills, business mentoring, and the growth and success of startups in West Java. Through a quantitative analysis involving 120 startups, the research employs structural equation modeling (SEM-PLS) and hypothesis testing to unravel the intricate relationships within the entrepreneurial ecosystem. The results reveal a positive correlation between entrepreneurial skills and startup growth, emphasizing the catalytic role these skills play in business expansion. Additionally, the study affirms the significant impact of effective business mentoring on both entrepreneurial skills development and overall startup success. The findings provide valuable insights for policymakers, mentors, and entrepreneurs, suggesting targeted interventions to foster a robust entrepreneurial ecosystem in the region.